Pengaruh Pelatihan Kerja Dan Disiplin Kerja Terhadap Kinerja Karyawan Pada PT PLN (PERSERO) UPDK Mahakam Samarinda - Heldina Pristanti; Trie Mega Octaviani; Satryawati Satryawati (Politeknik Negeri Samarinda, 2021)
Employee performance is very important in supporting the progress of the company. Performance is one of the important things for the company because it is related to the activities carried out. Good performance and focus can provide good profits for the company and employees. This research was conducted to determine the effect of job training and work discipline at PT PLN (Persero) UPDK Mahakam. The population involved in this study were employees of PT PLN (Persero) UPDK Mahakam who attended the training with a total of 40 respondents. This research is a quantitative research. The analytical tool used is the SPSS version 17 application. The independent variable (variable X) of this study is job training and work discipline, while the dependent variable (variable Y) is employee performance. The results of this study indicate that: (1) Job training has no significant effect on employee performance. (2) Work discipline has a significant effect on employee performance.